110 Risk of mortality in heart failure admissions in weekend and bank holidays. (6th June 2022) - Masudi, Sundas Tahir; Joseph, Prince Josiah; Reham, Awad; Rahman, Amna; Bahar, Jameela; Owen, Emily; Khan, Shamshad; Hilal-Babu, Mohammed; Avinash, Sunita; Wong, Kenneth
Abstract : Introduction: The weekend effect occurs as a result of the failure of healthcare provision to improve processes of care, including ensuring 24/7 access to life-saving diagnostic and therapeutic procedures such as echocardiography in patients with heart failure (HF). Increased mortality has been linked to weekend patient admissions globally thus it is important to understand its impact on HF patients and subsequently the changes that can be implemented to improve quality of care for weekend admissions. Methods: A retrospective study of consecutive admissions with HF as first diagnostic position in Blackpool Victoria Hospital from 1st August 2019 to 31st January 2021, with admission time and date recorded. Normal working hours is defined as 9am to 5pm during weekdays except UK Bank holidays. The primary endpoint was index episode mortality. Secondary endpoints were readmission within 60 days and the composite endpoint of death and readmission within 60 days of admission.Results:609 patients were admitted with HF. 426 of these patients were admitted on a weekday, whilst 183 were admitted on the weekend or bank holiday. There was no significant difference in baseline characteristics between the 2 cohorts [Table 1]Thirty-eight patients (8.9%) admitted during the weekday died. By contrast, 9 of 183 (4.9%) patients admitted during the weekend or bank holiday died [p=0.099]. Significantly higher proportion of weekday admitted patients experienced the composite endpoint of death and readmission within 60 days of admission (38% vs 27%, p=0.014). Death within 60 days after admission was also significantly higher for weekday admissions [79 patients (19%) vs 21 patients (11%) (p=0.031)]. Readmission within 60 days was also significantly higher after weekday admission [108 (25%) vs 32 (17%), p=0.037]. There is no significant difference between the 2 cohorts in appropriate use of disease modifying drugs. There is no difference in the number of echocardiogram performed within 48 hours of admission (weekday admission: n=150, 35%; weekend/bank holiday: n=65, 36%; p>0.99). If the echocardiogram was not completed within 48 hours, the median number of days it took for patients admitted on both the weekday and the weekend to get the echocardiogram was 4 days [weekday admission: 4 days, interquartile range (IQR) 4–6 days; weekend admission: 4 days, IQR 3–5 days), p=0.039]. Conclusion: Survival and readmission outcomes were surprisingly better in patients who were admitted over the weekend or bank holiday vs weekday. Future multicentre studies are merited to better understand the weekend effect and its impact on the care of HF patients Conflict of Interest: None